1976
DOI: 10.1159/000122607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dorsal Fornix Section and Hippocampectomy on Adrenocortical Responses to Sensory Stimulation in the Rat

Abstract: With the purpose of identifying the neural structures which are involved in the mediation of the adrenocortical responses to photic, acoustic and sciatic nerve stimulation, experiments were conducted on male rats with bilateral section of the dorsal fornix and dorsal or ventral hippocampectomies. The basal corticosterone levels in these animals were not significantly different from those in controls. Stimulation of the 3 sensory modalities produced normal adrenocortical responses in rats with fornix section. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

1976
1976
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 2 publications
3
15
0
1
Order By: Relevance
“…Furthermore, the effect of the dentate lesions appeared to be specific for behavioral stress, when one considers that the dentatelesioned animals did not differ from intacts with respect to their adrenal response to either laparotomy or ether stress. The data for ether stress presented here are similar to the results obtained, with hippocampally lesioned rats, by Conforti and Feldman [2] and by Lanier el al. [15], More over, in agreement with these authors as well as luvone and Van Hartesveldl [9], dentate lesions did not alter the plasma corticosterone levels in nonstressed animals.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the effect of the dentate lesions appeared to be specific for behavioral stress, when one considers that the dentatelesioned animals did not differ from intacts with respect to their adrenal response to either laparotomy or ether stress. The data for ether stress presented here are similar to the results obtained, with hippocampally lesioned rats, by Conforti and Feldman [2] and by Lanier el al. [15], More over, in agreement with these authors as well as luvone and Van Hartesveldl [9], dentate lesions did not alter the plasma corticosterone levels in nonstressed animals.…”
Section: Discussionsupporting
confidence: 92%
“…on steroid-sensitive pathways activated during stress. One im portant steroid-sensitive site implicated in the stress re sponse is the hippocampus [2,4,20,21]. We show here a differential effect of 17a-OH-progesterone and I l-epicortisol in competing for corticosterone binding sites in this tis sue, with the former being some 100 times more potent than the latter in this regard.…”
Section: Discussionmentioning
confidence: 63%
“…The previously reported increase in corticosterone concentration may reflect disruption of fibers passing through or around the lesioned area. The failure of other studies to determine such an effect (Coover et al, 1971;Lanier et al, 1975;Conforti and Feldman, 1976;Smotherman et al, 1981;Bradbury et al, 1993;Herman et al, 1995) may not have been a reflection of incomplete damage to the hippocampus. One possibility is that nonselective mechanical or electrolytic lesions of the hippocampus disrupted rostrally oriented fibers from the ventral subiculum.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown that damage to the hippocampus increases basal glucocorticoid secretion (Fendler et al, 1961;Kim and Kim, 1961;Knigge, 1961;Moberg et al, 1971;Fischette et al, 1980;Wilson et al, 1980;Sapolsky et al, 1984Sapolsky et al, , 1991Herman et al, 1989), but these lesions were made either by aspiration or by transection of the fimbria-fornix and caused damage to bypassing fibers as well as adjacent brain systems, including the parahippocampal cortices and several subcortical structures. Other studies failed to identify a hippocampal inhibitory influence on the HPA axis (Coover et al, 1971;Lanier et al, 1975;Conforti and Feldman, 1976;Smotherman et al, 1981;Bradbury et al, 1993;Herman et al, 1995) but there was only incomplete damage to the hippocampus in these studies. The remaining tissue may have been sufficient to maintain hippocampal feedback inhibition of the HPA axis.…”
Section: Introductionmentioning
confidence: 87%